Cryogenic platform for coupling color centers in diamond membranes to a fiber-based microcavity - Salz, Marcel; Herrmann, Y.; Nadarajah, A.; Stahl, A.; Hettrich, M.; Stacey, Alastair; Prawer, Steven; Hunger, David; Schmidt-Kaler, F. (Applied Physics B-Lasers and Optics, 2020)
We operate a fiber-based cavity with an inserted diamond membrane containing ensembles of silicon vacancy centers (SiV-) at cryogenic temperatures ≥4K. The setup, sample fabrication and spectroscopic characterization are described, together with a demonstration of the cavity influence by the Purcell effect. This paves the way towards solid-state qubits coupled to optical interfaces as long-lived quantum memories.
CRIS-Team Scopus Importer:2023-03-27